Media, movements, and political change - Earl, Jennifer, 1974-; Rohlinger, Deana A. (Emerald, 2012)
This volume of Research in Social Movements, Conflicts and Change explores the relationships between mass media, social movements, and political change. Since Martin Luther nailed his Theses of Contention on the Wittenberg Church door in 1517, scholars and pundits have noted that the media plays an important role in social and political change. This volume advances scholarly understanding of how activists and elites alike use books, newspapers, and Internet-enabled technologies to affect change. Chapters include analyses of the role of media in the (Anti-)Abortion, Globalization, Labor, Townsend, and White Power movements as well as Barack Obamas 2008 campaign. Altogether, this volume suggests new avenues for research, provides new insights into the strategic use and influence of media, and challenges existing assumptions of media-movement relationships.
Keywords: Political Science -- Political Process -- General.; Social Science -- Sociology -- General.; Politics & government.; Political campaigning & advertising.; Social movements.; Mass media -- Political aspects.; Communication in social action.; elektronické knihy; electronic books